GAGASAN ACEH BARU: PEMBENTUKAN IDENTITAS ACEH DARI DALAM REAKTUALISASI RUANG PUBLIK BAGI AKSI PENGELOLAAN KEARIFAN LOKAL PASCA-KONFLIK DAN TSUNAMI - Mujib, Ibnu (Jurnal Kawistara, 2014)
This paper quests the new Acehness identity that inspiring lokal revival in Aceh. Two important thingsthat would support the thesis how the ideas of new Aceh or Aceh revival are formulated from within?At least, the strengthening of public space as a local knowledge base management becomes an importantdiscourse in the course of the indicator measuring the local revival in Aceh. In addition, the process offormation of Acehnese identity is also one of the research questions of this paper, in which this practicehas marked the end of a local revival is being formulated in Aceh. Therefore, the questions about theprocess of dialogue and negotiation as what is growth in Aceh recently, will be discussed in this research.This research shows that the reactualization of public spaces that has been sunk by the conflict or thetsunami, now it is resurrected to turn the social bases that have been lost and even blurred. Whail,local wisdom and its discourse had reached the implementation of the policy through a qonun as aform of maintenance an intellectual heritage of Aceh to be kept alive and implemented. Communalconsciousness constructed by the fact that many of these actors have been integrated through variousforms of dialogue and long negotiation. So donât be surprised if the recent in-meunasah, gampong orvillage activities turn on the mosque as a center of Islamic studies, and even coffee shops also determinethe direction of Acehnese identity is being created, especially as the idea of Aceh revival.